The Impact of Negative Endorser Information and their Facial Appearance on Advertising Effectiveness for Profit and Not-for-Profit Organizations. Issue 2 (15th March 2017) - Roozen, Irene; Raedts, Mariet
ABSTRACT: This study compared consumer reactions to positive and negative information about endorsers. We analysed the effects of positive versus negative publicity about a fictitious male or female endorser with either a cold or warm facial appearance in two conditions: an ad for a profit organization and an ad for a nonprofit organization. The results show that consumers' attitude toward the ad and the brand/charity organization is negatively affected by negative information about the endorser. Moreover, the impact of negative information of the same endorser is significantly greater for ads of profit organizations than for ads of not-for-profit organizations, especially for endorsers with a warm facial appearance. These results suggest that the risk of negative endorser information is much higher for profit organizations than for not-for-profit organizations.